Inflation and unemployment trade-off: A re-examination of the Phillips curve and its stability in Nigeria - Hizir Sofyan; Muhammad Shabri Abdul Majid; Moh. Rizky Rahmanda (Contemporary Economics, 2019)
Although the maintenance of price stability and the attainment of full employment are important macroeconomics goals in any economy, Nigeria still contends with problems of high inflation and unemployment. This study examines the Phillips curve hypothesis (inflation and unemployment trade-off) and its stability in Nigeria from 1980 to 2016 using the Autoregressive Distributed Lag (ARDL) bounds testing approach. Other estimation techniques including the Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), Static Ordinary Least Squares (OLS), and Canonical Cointegrating Regression (CCR) were employed to ascertain the consistency and robustness of the results that were generated using the ARDL bounds testing method. The results of the cointegration test reveal the existence of a long-run relationship between inflation and unemployment. The results of the ARDL bounds testing, FMOLS, DOLS, static OLS and CCR estimations indicate that there is a trade-off relationship between the variables, and higher unemployment leads to lower inflation in the long-run. The plots of the cumulative sum of squares of recursive residuals (CUSUMQ) confirm the stability of the long-run parameters. The results of the causality test using the standard Granger causality test and the Toda and Yamamoto approach demonstrate that there is unidirectional causality from inflation to unemployment. Based on these findings, this study recommends policies to reduce both inflation and unemployment.
Keywords: D82; M14; M30; 330; Inflation; Unemployment; Phillips Curve; Nigeria